1994
DOI: 10.1126/science.263.5154.1747
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Atmospheric Circulation and Ocean Ice Cover over the North Atlantic During the Last 41,000 Years

Abstract: High-resolution, continuous multivariate chemical records from a central Greenland ice core provide a sensitive measure of climate change and chemical composition of the atmosphere over the last 41,000 years. These chemical series reveal a record of change in the relative size and intensity of the circulation system that transported air masses to Greenland [defined here as the polar circulation index (PCI)] and in the extent of ocean ice cover. Massive iceberg discharge events previously defined from the marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
208
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(223 citation statements)
references
References 17 publications
11
208
0
4
Order By: Relevance
“…These fluctuations in sea-water temperature, that are linked by these authors to fluctuations of the polar circulation index (Mayewski et al, 1994), certainly have an impact on deep-water formation and cascading as observed nowadays.…”
Section: Multi-events Hypothesismentioning
confidence: 73%
“…These fluctuations in sea-water temperature, that are linked by these authors to fluctuations of the polar circulation index (Mayewski et al, 1994), certainly have an impact on deep-water formation and cascading as observed nowadays.…”
Section: Multi-events Hypothesismentioning
confidence: 73%
“…Having said that, nitrate is rare in having very similar average concentrations in the LGM and the Holocene; changes can be seen [49] at the glacial termination, but they are tiny compared with the vast factorial changes in all other chemical content. Nitrate does show clear annual cycles that are used as a component of the layer-counted dating of Greenland ice cores.…”
Section: The Long Perspective: Nitratementioning
confidence: 99%
“…In lieu of independent measures of chloride mass deposition history, a constant value of chloride mass deposition is typically used in CMB analysis with caveats regarding the failure of this assumption [e.g., Scanlon, 1991]. Ice core data indicates that atmospheric chloride deposition was lower over Greenland during the Holocene compared to that during the late Pleistocene [Mayewski et al, 1994]. Chloride in the atmosphere arises from sea salts; therefore major paleoclimatic shifts in prevailing wind patterns that occurred during glaciation on northern continents [Thompson et al, 1993] [1986] reported anion velocities that were double the velocity of water at a clay loam field site, while at a sandy soil site the water and anions had almost the same velocity.…”
Section: Model Assumptionsmentioning
confidence: 99%